Intoleransi Antar Umat Beragama Di Media Sosial (Studi Pada Youtube Deddy Corbuzier Program Log In – Eps 30 “Toleransi, Kita Cetak Sejarah) - Childa Tanzilul Hidayah; Kun Kun Kurniawan (IAIN Padangsidimpuan, 2025)
This study examines the representation of interfaith communication in social media content through an analysis of the Log In program episode 30 entitled